(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2024)
The use of cold-formed steel members as structural columns and beams in residential, industrial and commercial building was increased significantly in recent time. This study is focused on the use of cold-formed steel sections as flexural member subjected to lateral torsional buckling. For this purpose a software ANSYS program was developed and validated using available numerical and experimental results. This paper presented the results of finite element analysis for cold-formed channel cross-section and the comparisons with AISC and Australian design rules. Failure in cold-formed steel beams is generally initiated by one of three instabilities: local, distortional, or lateral-torsional buckling. The results indicated that the value of maximum ultimate load occurs due to point load act on the shear center, the percent of increasing about (35.84%). Due to differences in the degree of cold working in the flat parts and the corner regions, the mechanical properties vary over the cross-section. In cold-formed channel beam, the lateral torsional buckling moment occurs between elastic and inelastic critical moment . The convergence about (97.83%) with the experimental data and (89.78%) with the numerical results.